MODERNISASI PEMERINTAHAN PRAJA MANGKUNAGARAN SURAKARTA - Wasino, Wasino (Paramita: Historical Studies Journal, 2012)
Mangkunagaran is one of government and cultural center of Java in the Dutch colonial period. It was formed in 1757 through Salatiga Agreement, as product of Jawa War succession. At the beginning Praja Mangkunagaran was a district of Kasunanan, then it raised into a small empire. Government modernization was done since Mangkunagara IV by establishing some new institution. Increasingly sophisticated modernization carried out in the early twentieth century during the reign of Mangkunagara VI and Mangkunagara VII. Modernization of gover-nance is heavily influenced by the Dutch colonial governance combined with Javanese culture. The rise of new governance generates new identity that is different from another Javanese culture center. Key words: modernization, governance, MangkunagaranÃÂ  Mangkunagaran merupakan salah satu pusat pemerintahan dan budaya Jawa pada masa Kolonial Belanda. Ia terbentuk pada tahun 1757 melalui perjanjian Salatiga, sebagai hasil perang suksesi di Jawa. Praja ini semula hanya merupakan sebuah kabupaten, namun dalam perkembangannya berkembang menjadi sebuah kerajaan kecil. Modernisasi pemerintahan dilakukan sejak Mangkunagara IV dengan membentuk lembaga-lembaga kerajaan yang berbeda dengan Kasunanan Surakarta. Modernisasi semakin canggih dilakukan pada awal abad XX pada masa pemerintahan Mangkunagara VI dan Mangkunagara VII. Modernisasi tata pemerintahan banyak dipengaruhi oleh tata pemerintahan Kolonial Belanda dipadukan dengan kebudayaan Jawa. Lahirnya tata pemerintahan baru menghasilkan identitas baru yang berbeda dengan pusat-pusat budaya Jawa lain, Kasunanan dan Paku Alaman. Kata kunci: modernisasi, pemerintahan, Mangkunagara ÃÂ